(untitled) (International Journal of Food and Nutritional Sciences, 2019)
With the goal of achieving sustainable agriculture and guaranteeing food security in the face of climate change, climate-smart agriculture is a method to creating agricultural strategies to modernize agricultural systems utilizing digital tools. This article provides a thorough assessment of the literature on robots, the Internet of Things, and remote sensing as "smart agricultural technologies" for Cyprus’s climate-smart agriculture.